Exosomes derived from heat shock preconditioned bone marrow mesenchymal stem cells alleviate cisplatin-induced ototoxicity in mice - Tao Yang; Wei Li; Anquan Peng; Qin Wang (Journal of Biological Engineering, 2022)
Abstract NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome contributes to the development of cisplatin-induced ototoxicity. Whether heat shock pretreatment could be utilized to up-regulate 70 kilodalton heat shock proteins (HSP70) expression in bone marrow mesenchymal stem cells (BMSCs)-derived exosomes (HS-BMSC-Exo) to alleviate cisplatin-induced ototoxicity is deciphered in this study. Heat shock pretreatment was performed on BMSCs to induce HS-BMSC-Exo, which were further trans-tympanically administrated into cisplatin intraperitoneally injected C57BL/6 mice. Auditory brainstem response (ABR) was assessed to indicate auditory sensitivity at 8, 16, 24, and 32 kHz. Myosin 7a staining was utilized to detect the mature hair cells. The relative expressions of the NLRP3 inflammasome complex were determined with Western blot in the cochlea. Diminished auditory sensitivity and increased hair cell loss could be observed in the cisplatin exposed mice with increased content of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, NLRP3, ASC, cleaved caspase-1, and pro-caspase-1, and decreased content of IL-10, which could be reversed by HS-BMSC-Exo or BMSC-Exo administration. It was worth noting that HS-BMSC-Exo demonstrated more treatment benefits than BMSC-Exo in cisplatin-induced ototoxicity. Heat shock precondition may provide a new therapeutic option to produce exosomal HSP70, and HS-BMSC-Exo could be utilized to relieve cisplatin-induced ototoxicity.